Maternal Role Confusion: Relations to Maternal Attachment and Mother–Child Interaction from Infancy to Adolescence. Issue 2 (25th January 2013) - Vulliez‐Coady, Lauriane; Obsuth, Ingrid; Torreiro‐Casal, Monica; Ellertsdottir, Lydia; Lyons‐Ruth, Karlen
Abstract Self‐reports of role confusion with the parent in childhood are associated with a variety of adverse outcomes. However, role‐confusion has been studied primarily from the point of view of the child. The current study evaluated an instrument for assessing role confusion from maternal interviews rather than from child observations or self‐reports in adulthood. Fifty‐one mothers participating in a longitudinal study since their own child's infancy were administered the Experiences of Caregiving Interview (C. George & J. Solomon, 1996) when the child was age 20. Interviews were coded using the newly developed Parental Assessment of Role Confusion (PARC; L. Vulliez‐Coady & K. Lyons‐Ruth, 2009). Maternal PARC scores were related to observational measures of role‐confusion in interaction with the child both in infancy and late adolescence. PARC scores also were related to mothers' hostile‐helpless states of mind on the Adult Attachment Interview (C. George, N. Kaplan, & M. Main, 1984, 1985, 1986) and to the extent of Unresolved loss, but not Unresolved Trauma. PARC scores also were related to mothers' self‐reports of helplessness experienced in the parenting role. Discriminant validity of the PARC was demonstrated in that role confusion on the PARC was not related to hostile or disoriented forms of parent–child interaction. Implications for clinical assessment of role confusion are discussed.